PC.121 The Different Presentations and Management of Congenital Cytomegalovirus Infection – A Case Series. (9th June 2014) - Murphy, AP; Nesbitt, V; Babarao, S; Kamalnathan, A
Abstract : Introduction: Congenital Cytomegalovirus (CCMV) infection is the most common intrauterine infection. We present three cases of babies and compare their symptoms and subsequent management. Treatment of CMV is with antivirals. The aim is to avoid end-organ damage. We highlight the difficulties in recognising and managing CCMV which is refactory to first line treatment. We identify the issues of differentiating between CCMV complications and side-effects of antivirals. Results: All babies were diagnosed postnatally, from day 2–42 of life. One baby was diagnosed due to symmetrical intrauterine growth retardation, another following tests for petechiae/thrombocytopenia. The last baby was diagnosed following a clinical decline; thought to be infection. Babies were treated with platelet transfusions (average of 1 unit/week). All three babies received an eight week treatment of ganciclovir; with viral loads subsequently falling. One of the babies deteriorated a fortnight after the end of ganciclovir with increased viral loads. Second-line antiviral (Foscarnet) was commenced. Signs of bone marrow suppression were found during treatment, it was unclear whether this was secondary to resurgent CCMV or Foscarnet. End organ damage was evident in two of the three patients; both have a 'moderate' degree of unilateral hearing loss, one of these two has changes on MRI scan consistent with polymicrogyria. Conclusion: CCMV infection has a varied presentation and can be resistant to first line antiviral agents. Little literature exists in use of Foscarnet in the neonatal cohort and difficulties in identifying causes of complications makes management difficult.